Stanley Cavell and the New North-American Philosophy - Nadal, Alex R. (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
This article aims at a concise and modest presentation of the so-called ordinary language philosophy by an author generally unknown in our country, but whom many already consider as indispensable in the contemporary philosophical scene; likewise, it is an attempt to overcome, or to compensate for, the intellectual gap from which our country lamentably still suffers. For this, I will present some orientating coordinates of North-American philosophy to contextualize this peculiar and important author.
Keywords: North-American philosophy; Stanley Cavell; ordinary language; H. Putnam.